The influence of matrix metalloproteinase -2, -9, and -12 promoter polymorphisms on Iranian patients with oesophageal squamous cell carcinoma - Eftekhary, Haniehsadat; Ziaee, Abed-Ali; Yazdanbod, Mansour; Shahpanah, Mitra; Setayeshgar, Aziz; Nassiri, Mojgan (Contemporary Oncology/Współczesna Onkologia, 2015)
Aim of the study : Matrix metalloproteinases (MMPs) are a zinc-dependant endopeptidase family that can degrade extracellular matrix components. Their dysregulation has been proven in several diseases, including cancer. Genetic variations in MMP promoter regions can alter their expression. The aim of the present study is to investigate the correlation of MMP-2 (-1306C/T), MMP-9 (-1562C/T), and MMP-12 (-82A/G) single nucleotide polymorphisms (SNPs) with oesophageal squamous cell carcinoma (ESCC) initiation and progression susceptibility in Iranian patients. Material and methods : MMP-2 (-1306C/T), MMP-9 (-1562C/T), and MMP-12 (-82A/G) SNPs were detected using polymerase chain reaction-restriction fragment-length polymorphism (PCR-RFLP) technique in 70 patients and 60 healthy controls. The genotypes and allele distributions were statistically compared in patients and controls. The correlation of MMP-2 (-1306C/T) and MMP-9 (-1562C/T) polymorphisms with clinicopathological features were investigated in 53 patients. Results: No statistically significant differences were observed in genotype and allele frequencies of MMP-2 (-1306C/T) and MMP-9 (-1562C/T) between patients and controls (p > 0.05). In addition, no relevance was observed in MMP-2(-1306C/T) and MMP-9 (-1562C/T) SNPs and clinicopathological features. There was no nucleotide variation in MMP-12 (-82) in the case and control groups. Conclusions : This study indicates that these three SNPs may have no significant association in ESCC risk in Iranian patients.